The Effect of Traffic on Wheel Flange Wear of LRT Jabodebek - Zulkarnain, Akbar; Ersaputra, Arya Yudha; Atmaja, Dadang Sanjaya; Rifai, Afaf Fadhil; Pradana, Adrian (Journal of Railway Transportation and Technology, 2024)
Light Rail Transit (LRT Jabodebek) is a light rail train that serves 2 operational crossings, namely cibubur Line and Bekasi Line. The problem that occurs in Jabodebek LRT is abnormal wheel flange wear. This problem will have an impact on the wheel life to be shorter. Therefore, this study aims to analyze the cross that has the most influence on the wear rate of the Jabodebek LRT wheel flange and find out when turning will be carried out. The flange measurement data obtained from daily and monthly maintenance data will be analyzed using the simple linear regression method. The value of flange wear caused by Lintas Harjamukti-Dukuh Atas of 0.00285 mm in one trip is greater than Lintas Jatimulya-Dukuh Atas of 0.001295 mm. While trainset 1 will be turned after traveling 117,962 km or 3944 trips, trainset 2 will be turned after traveling 74,061 or 2424 trips, trainset 13 will be turned after traveling 237,295 km or 7908 trips, trainset 18 will be turned after traveling 85,911 km or 2707 trips. Therefore, the Harjamukti-Dukuh Atas section has a greater influence on the wear that occurs compared to the Jatimulya-Dukuh Atas section.